Experiential and Spirituality-Based Character Education: A Study of the Thought of John Dewey and Al-Ghazali - El-Muhtadi Rizal, Zacky Al-Ghofir; Selfiana, Dian; Najah, Sabilul; Hidayah, Nabila Salsa; Farahsya, Isna (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
This research aims to examine and compare in depth the thinking of John Dewey and Al-Ghazali in the context of character education, focusing on the empirical experiential approach according to Dewey and the spiritual-moral approach according to Al-Ghazali. John Dewey, as a leading figure of Western progressive education, developed the concept of experiential learning that placed direct experience and social interaction as the foundation of the formation of students' morals and personalities. Meanwhile, Al-Ghazali emphasized that character education must lead to the purification of the soul (tazkiyat al-nafs) through the application of the values of the Qur'an and Sunnah, as well as the habit of pious deeds. Through a qualitative method with a literature study approach and descriptive-comparative analysis, this study identifies the principles of character education of the two characters, as well as explains the fundamental similarities and differences in their views. The results show that although they differ in philosophical grounds—Dewey is secular-humanist while Al-Ghazali is religious-transcendental—both agree that character education should be holistic, involving the active processes of the individual, the environment, and life experiences. The novelty of this research lies in the systematic integration between two educational paradigms that have been considered opposite. By bringing together Dewey's principle of learning by doing and the concept of tahdzib al-nafs Al-Ghazali, this study offers a new theoretical framework for a balanced model of character education between rational, social, and spiritual aspects. This contribution is important in responding to the challenges of modern education that demand not only intellectual intelligence, but also emotional and moral intelligence.